TINJAUAN HUKUM PENDAFTARAN TANAH SECARA SISTEMATIS MELALUI AJUDIKASI BERDASARKAN PP NO. 24 TAHUN 1997 - Raras Laila Yustinov, Fitika Andraini (Jurnal Ilmiah Dinamika Hukum, 2019)
The need for land continues to increase so that it often causes very complex problems. To deal with these land issues, the government issued Law no. 5 of 1960 concerning Basic Agrarian Principles which later became known as the UUPA, the birth of the UUPA was a new milestone for this nation in land law. In line with that, the government then issued government regulation No. 24 of 1997 concerning land registration which reaffirmed the importance of the community registering their land, land registration functions to find out the status of the land parcels, who owns it, what rights are it, how much area, what is it used for. The importance of systematic, good and correct land registration through adjudication aims to reduce problems that arise with regard to land. The research method used by the writer is a juridical empirical approach with the intention of proving or testing to ensure the truth and rationalizing it through the results of research and experiences that have been found in everyday life. The results of the research found that more people register their land in a sporadic manner, because the community considers that systematic land registration does not necessarily occur every year, even though it is expensive for the community to register their land in order to obtain the rights to the land they own. Keywords: PP No. 24 of 1997, land registration, adjudication